Evaluation of nurses’ knowledge toward pain management of leukemic child under chemotherapy - ahjil, Zaid; Maala, Ekbal (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): To evaluate nurses’ knowledge toward pain management of leukemic child in oncology wards how were receiving chemotherapy. Methodology: A descriptive study was conducted in two hospitals on (40) nurses, who provided care for the children with leukemia in oncology wards (2) hospitals (Children Welfare Teaching Hospital and Child’s Central Teaching Hospital) in Baghdad city from October 2010 up to the 27th of October 2011 for the purpose of evaluating their knowledge towards pain management for leukemic child. A purposive "non-probability sample" was selected that consisted of (40) nurse who are working in oncology wards. A questionnaire format was used which consist of (2) parts, the first part includes demographic information of the sample and the second part consists of structured Items concerning nurses’ knowledge toward pain management for leukemic child which includes (3) main sections and comprised of (89) Items. Reliability and validity of questionnaire was estimated through a pilot study and a panel of expert. The data were analyzed by using descriptive statistical measures which included frequencies, percentages, and standard deviation, as well as the use of inferential statistical measures which include the chi- square test. Results: The results revealed inadequate nurse’s knowledge about pain management for leukemic child under chemotherapy, two third (75 %) of the sample has poor knowledge toward pharmacological and non pharmacological pain management methods. Recommendations: Based on the results of research, the study recommends initiating training courses in pain management and developing pain assessment tools for assessing child’s pain and evaluating the level of pain management procedures